Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1111/j.1432-2277.2006.00356.x
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative fluid management in renal transplantation: a narrative review of the literature

Abstract: Summary Adequate volume maintenance is essential to prevent acute renal failure during major surgery or to ensure graft function after renal transplantation. The various recommendations on the optimum fluid therapy are based, at best, on sparse evidence only from observational studies. This article reviews the literature on perioperative fluid management in renal transplantation. Crystalloid solutions not exerting any specific side‐effects are the first choice for volume replacement in kidney transplantation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
72
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(75 citation statements)
references
References 141 publications
1
72
1
1
Order By: Relevance
“…Two small randomized trials - one in patients with pre-existing normal renal function [65], the second in patients with established renal dysfunction [66] - did not find differences for any measured variable of renal function. More convincing are the results obtained with the preventive administration of mannitol, just before clamp release, during renal transplantation [67,68]. The sparse controlled data available have shown that 250 ml of 20% mannitol given immediately before vessel clamp removal reduces the incidence of post-transplant AKI, as indicated by a lower requirement of post-transplant dialysis.…”
Section: Recommendations and Rationalementioning
confidence: 99%
“…Two small randomized trials - one in patients with pre-existing normal renal function [65], the second in patients with established renal dysfunction [66] - did not find differences for any measured variable of renal function. More convincing are the results obtained with the preventive administration of mannitol, just before clamp release, during renal transplantation [67,68]. The sparse controlled data available have shown that 250 ml of 20% mannitol given immediately before vessel clamp removal reduces the incidence of post-transplant AKI, as indicated by a lower requirement of post-transplant dialysis.…”
Section: Recommendations and Rationalementioning
confidence: 99%
“…Colloids may be considered in recipients with severe intravascular volume deficits who require high-volume resuscitation [49]. Albumin, a normal endogenous colloid with a wide safety margin is recommended with large fluid deficit.…”
Section: Anesthetic Managementmentioning
confidence: 99%
“…Albumin, a normal endogenous colloid with a wide safety margin is recommended with large fluid deficit. Synthetic colloids that have widely replaced albumin in clinical practice; dextrans, gelatins and solutions of hetastarch; do not seem to be preferable to albumin [49]. Colloids have been reported to adversely affect renal function and may increase bleeding complications [50].…”
Section: Anesthetic Managementmentioning
confidence: 99%
“…(4,5) These parameters can be achieved with the vigorous infusion of crystalloid solutions (C). (20) Eventually, the use of excessive fluid infusion becomes of value to avoid the use of vasopressors (D). (21,22) However, no controlled or retrospective studies have been done that specifically address the ideal method of fluid replacement for deceased donors.…”
Section: Renal Maintenancementioning
confidence: 99%